2022
DOI: 10.3389/fpsyg.2022.1032316
|View full text |Cite
|
Sign up to set email alerts
|

Motivation in second language acquisition: A bibliometric analysis between 2000 and 2021

Abstract: As one of the most important constructs of individual differences in second language learning, motivation has garnered a lot of attention in the area of Second Language Acquisition (SLA). Nevertheless, little bibliometric research has been conducted to provide a systematic overview of this line of research, which will help researchers to better understand how motivation-related research in SLA has evolved over the past 22 years and where it might push the boundaries of SLA research into in the future. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 62 publications
0
1
0
1
Order By: Relevance
“…The students' favorable attitude toward TikTok utilization for EFL learning evident in the present study might spill over into their increased motivation and such increased motivation might eventually influence their proficiency in English (Wu, 2022). The experimental study conducted by Gao et al (2023) showed that incorporating TikTok into MICE learning activities bring about positive impact on students' learning motivation and English oral proficiency.…”
Section: Free Tuitionmentioning
confidence: 58%
“…The students' favorable attitude toward TikTok utilization for EFL learning evident in the present study might spill over into their increased motivation and such increased motivation might eventually influence their proficiency in English (Wu, 2022). The experimental study conducted by Gao et al (2023) showed that incorporating TikTok into MICE learning activities bring about positive impact on students' learning motivation and English oral proficiency.…”
Section: Free Tuitionmentioning
confidence: 58%
“…Azken sei hamarkadetan, BHEko motibazioari buruzko ikerketa esponentzialki hazi da, ziur asko banakakoen desberdintasunei buruzko beste edozein arlo baino gehiago (Boo, Dörnyei eta Ryan, 2015, 145). Hori erakusten dute berriki egindako ikerketa sintetikoek (Boo, Dörnyei eta Ryan, 2015, Al-Hoorie, 2017 eta bibliometrikoek (Wu, 2022), 2000 eta 2021 arteko argitalpen-corpus bati buruzkoak. Bigarren mailako iturri horiek argitzen dute orain arte azterlan praktikoen gainetik azterlan teorikoak izan direla nagusi (Boo, Dörnyei eta Ryan, 2015, 149-150); gaur egun nagusi den ikuspegi teorikoa Nia-H2aren motibazio-sistema dela (Boo, Dörnyei eta Ryan, 2015, 153-154;Wu, 2022, 11-14); azterketa enpiriko gehienek motibazioa ikasleengan aztertu dutela, eta ez horrenbeste irakasleengan edo desgaitasunen bat duten ikasleengan , eta hirugarren mailako erakundeetan, gehienbat asiarretan, non ingelesa atzerriko hizkuntza gisa ikasten baitzen (Boo, Dörnyei eta Ryan, 2015, 151;Mahmoodi eta Yousefi, 2022, 282-283).…”
Section: Motibazioa Bigarren Mailako Iturrien Araberaunclassified